Grazing Studies in the Arid and Semi-Arid Zones of Rajasthan Vii. Utilization of Vegetation Cover, Grazing Behaviour of Sheep and Seasonal Variation of Crude Protein Content of Plants in Different Pastures - Chakravarty, A K; Ratan, Ram; Singh, K C (Annals of Arid Zone, 2016)
Grazing was conducted with adult ewes at the Central Research Farm, Jodhpur from the 15th August, 1966 to 30th June, 1967 in four different pasture paddocks, three of which were sown pastures of (I) Cenchrus ciliaris and Lasiurull sindicUs, (2) G. ciliaris and C. setigerus,(3) C. ciliaris, C. setigerus and L. sindicull and the fourth one was the natural and protected pasture. The extent of utilization of plant population was 38.7, 7.9, 52.2 and 47.1 per transect (10 metre sent in the paddocks I to 4 respectively against the respective plant population of 48.3, 20.S, 63.6 and 70.4 per transect in the paddocks. The perennial grasses viz., C. ciliaris. C.setigerUs, L.sindicus withstood the grazing stress well and there was an overall increase in their basal cover, ranging from 0.5 to 3 per transect in different pasture paddocks. C. setigerus was found to be most palatable among the perennial grasses where as Brachiaria ramcsa, Convolvulus microphyllu8, Indigofera cordifolia and I. linifolia were found to be more palatable among the annual species. Crude protein percentage of the perennial grasses varied from 9.2 to 2.8 per cent in different seasons of the year and it gradually decreased fromSeptember onwards Among the annual species Boerhavia diffusa, C. microphyllus, I. cordifolia and I linifolia recorded comparatively higher crude protein percentage of 17.3, 17.5 11.7 and 12.4 respectively.